Origin of enhanced stability and oxygen adsorption capacity of medium-sized Pt–Ni nanoclusters. (22nd June 2018) - Yang, Yang; Yu, Haiyan; Cai, Yushun; Ferrando, Riccardo; Cheng, Daojian
Abstract: Understanding the stability and adsorption properties of O atom can be considered as the first step to understand the mechanism of the oxygen reduction reaction on Pt–Ni nanoclusters. In this work, the equilibrium structures, stability, adsorption properties and deformation energies of medium-sized Pt–Ni nanoclusters are studied by global optimization method and density functional theory calculations. It is found that Pt–Ni nanoclusters are of more stable structure and larger oxygen adsorption energy than Pt nanoclusters, and the enhanced stability and oxygen adsorption capacity of Pt–Ni nanoclusters originate from both the strain and electronic factors. Based on the strain effect, the local pressures are on average much better equilibrated on Pt–Ni nanoclusters, bringing about the more stable structure. The elongation of the metal–metal bond distances results in the increase of adsorption energy of the O atom on Pt–Ni nanoclusters. Considering the electronic effect, the charge interaction between the LDOS (d orbital) of metal atoms adjacent to the adsorbed O atom and the DOS (p orbital) of the O atom gives rise to the increase of oxygen adsorption capacity on Pt–Ni nanoclusters. Simultaneously, the charge density difference analysis shows that the Ni atoms doping is conducive for O atom adsorption. In addition, the diffusion of O atom from surface to interior is difficult due to the high diffusion energy barriers. Our results show that both strain and electronic factors are of important effects on the stability and adsorption properties of nanoalloys.